Teaching Virtual Production in Higher Education: Lessons Drawn from the VPSN Research Project - Raimundo, Jos´e; Bessa, Diogo; Madureira, Marta (Proceedings of CAGA24: The Conference of AG Animation 2024, 2025)
Virtual production (VP) are technologies and processes to combine digital environments with physical stages to create content for entertainment industries like cinema. As teachers in related areas, we aim to keep our students up to date with VP skills, as they grow in demand from creative industries, and harnessing them requires significant learning commitment and financial investment. This paper presents a research project, the Virtual Production Studio Network (VPSN), which is aimed at addressing the previous demand, by providing knowledge resources and training. Drawn results from these activities enforce the idea that VP is not a universal solution to shooting films, and given its financial requirements, cost-effective alternatives must be sought to sustain learning. Independently of these challenges, VP holds immense potential, therefore we will keep pursuing ways to integrate its knowledge and technology into our lectures to augment the students' readiness in this field.